A study on how Perbadanan Usahawan Nasional Berhad (PUNB) motivation training program influence apprentice entrepreneurs self development / Mohd Amirul Afiq Ismail - Ismail, Mohd Amirul Afiq (Faculty of Business and Management, 2013)
This project paper about a study on how Perbadanan Usahawan Nasional Berhad (PUNB) motivation training program influence apprentice entrepreneurs self development.